# Trigonometri Question (HELP)

Bob19
Hi

I have this here Trigonometri function:

F(x) = Ax cos(x) + Bx sin(x) + C cos(x) + D sin(x)

where F'(x) = x cos(x)

I'm suppose to find A, B, C , D any hints or idears on how I do that?

Sincerely
Bob

Gold Member
Take the derivative of F(x). You know that F'(x)=x cos(x). This means the coefficient of (x cos(x)) should be 1. What can you say about the coefficients of all other terms?

Bob19
LeonhardEuler said:
Take the derivative of F(x). You know that F'(x)=x cos(x). This means the coefficient of (x cos(x)) should be 1. What can you say about the coefficients of all other terms?

Since its trigonometry then A,B,C,D can't higher than one?

F'(x) = A (cos(x) - x *sin(x)) + B(x *cos(x) + sin(x)) + C ( -sin(x)) + D(cos(x) = x cos(x)

But how I proced from here ?

/Bob

Homework Helper
Bob19 said:
Since its trigonometry then A,B,C,D can't higher than one?
No, these are just coefficients so they can be higher than 1.
It's cos(a) (and sin(a))) which are bounded between -1 and 1.

Bob19 said:
F'(x) = A (cos(x) - x *sin(x)) + B(x *cos(x) + sin(x)) + C ( -sin(x)) + D(cos(x) = x cos(x)

Your derivative seems correct, now just check what the coefficients have to be to get xcos(x).

Bob19
The best way of doing this is that to make the left side of the expression shorter ?

/Bob

TD said:
No, these are just coefficients so they can be higher than 1.
It's cos(a) (and sin(a))) which are bounded between -1 and 1.

Your derivative seems correct, now just check what the coefficients have to be to get xcos(x).

Homework Helper
Well, we have:

$$\begin{array}{l} F\left( x \right) = Ax\cos x + Bx\sin x + C\cos x + D\sin x \\ F'\left( x \right) = A\left( {\cos x - x\sin x} \right) + B\left( {\sin x + x\cos x} \right) - C\sin x + D\cos x \\ \end{array}$$

Rearranging gives:

$$F'\left( x \right) = \left( {A + D} \right)\cos x + \left( {B - C} \right)\sin x - Ax\sin x + Bx\cos x$$

We want this to equal $F'\left( x \right) = x\cos x$

So:

$$\left( {A + D} \right)\cos x + \left( {B - C} \right)\sin x - Ax\sin x + Bx\cos x = x\cos x$$

That should give a very simple system for the unknown coefficients A -> D

Bob19
TD said:
Well, we have:

$$\begin{array}{l} F\left( x \right) = Ax\cos x + Bx\sin x + C\cos x + D\sin x \\ F'\left( x \right) = A\left( {\cos x - x\sin x} \right) + B\left( {\sin x + x\cos x} \right) - C\sin x + D\cos x \\ \end{array}$$

Rearranging gives:

$$F'\left( x \right) = \left( {A + D} \right)\cos x + \left( {B - C} \right)\sin x - Ax\sin x + Bx\cos x$$

We want this to equal $F'\left( x \right) = x\cos x$

So:

$$\left( {A + D} \right)\cos x + \left( {B - C} \right)\sin x - Ax\sin x + Bx\cos x = x\cos x$$

That should give a very simple system for the unknown coefficients A -> D

Thanks then A = 0 , D = 0, B = C = 1

Right ?

/Bob